Research on the Yuan Universe Financial Trading Platform Under Innovative Business Model - Wang, Wei; Gao, Huaguo; Ren, Guanqiao; Luo, Lichang; An, Pengju; Jiang, Yachen; Jiang, Yachen (International Journal of Materials Science and Technology Studies, 2024)
This paper focuses on the innovative business model and its technology application of the Yuan-Universe financial trading platform. Firstly, the global trend and competitive status of cosmic finance are discussed through market analysis. Later, the paper analyzes in depth the role of Web3.0, blockchain and AI in improving the performance of the trading platform. In the business model section, this paper discusses the profit models such as transaction withdrawal and information consulting, and evaluates their financial sustainability. In addition, the paper analyzes the potential technical and market risks of the platform and discusses the management strategies. Finally, the paper summarizes the business and technological innovation of the yuan universe financial trading platform, and prospects the future development. This study provides insights for understanding new models of financial services and provides reference for the development of fintech.